2018
DOI: 10.1073/pnas.1814434115
|View full text |Cite
|
Sign up to set email alerts
|

BRI1 controls vascular cell fate in the Arabidopsis root through RLP44 and phytosulfokine signaling

Abstract: SignificanceCell-fate determination and cellular behavior in plants rely mainly on positional information and intercellular communication. A plethora of cues are perceived by surface receptors and integrated into an adequate cellular output. Here, we show that the small receptor-like protein RLP44 acts as an intermediary to connect the receptors for two well-known signaling molecules, brassinosteroid and phytosulfokine, to control cell fate in the root vasculature. Furthermore, we show that the brassinosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(151 citation statements)
references
References 71 publications
7
136
2
Order By: Relevance
“…Interference with HG de-methylesterification triggers BR signaling: overexpression of a PME inhibitor protein or exposing plants to epigallocatechin gallate (EGCG), a chemical that inhibits PME activity, impairs directional organ growth, a phenotype caused by an activation of BR signaling (Wolf et al, 2012b). RECEPTOR-LIKE PROTEIN44 (RLP44) interacts with the BR receptor BRASSINOSTEROID INSENSITIVE1 (BRI1) and the co-receptor BRI1-ASSOCIATED RECEPTOR KINASE (BAK1), likely acting as a scaffold to increase the association between BRI1 and BAK1 (Wolf et al, 2014;Holzwart et al, 2018). RLP44 is also essential for BR-mediated response to altered HG demethylesterification (Wolf et al, 2014).…”
Section: Downstream Signaling Eventsmentioning
confidence: 99%
“…Interference with HG de-methylesterification triggers BR signaling: overexpression of a PME inhibitor protein or exposing plants to epigallocatechin gallate (EGCG), a chemical that inhibits PME activity, impairs directional organ growth, a phenotype caused by an activation of BR signaling (Wolf et al, 2012b). RECEPTOR-LIKE PROTEIN44 (RLP44) interacts with the BR receptor BRASSINOSTEROID INSENSITIVE1 (BRI1) and the co-receptor BRI1-ASSOCIATED RECEPTOR KINASE (BAK1), likely acting as a scaffold to increase the association between BRI1 and BAK1 (Wolf et al, 2014;Holzwart et al, 2018). RLP44 is also essential for BR-mediated response to altered HG demethylesterification (Wolf et al, 2014).…”
Section: Downstream Signaling Eventsmentioning
confidence: 99%
“…To decipher the contribution of individual putative phosphorylation sites to RLP44 function, we mutated each of the sites individually to alanine in RLP44-GFP and quantified the capacity of these constructs to complement cnu2. We reasoned that working with near endogenous expression levels might increase the sensitivity of the complementation assay, therefore all RLP44-GFP variants were driven by the RLP44 promoter (Holzwart et al, 2018b). To assess comparability between the previously characterized overexpression lines, we also generated RLP44 promoter-driven Pdead and Pmimic versions, in which all four putative phosphosites are mutated as previously described.…”
Section: Phosphorylation At Individual Sites Has Opposing Effects On mentioning
confidence: 99%
“…Basic fuchsin staining of five-day-old seedling roots and CLSM analysis was performed as described (Holzwart et al, 2018b).…”
Section: Xylem Cell Number Analysismentioning
confidence: 99%
“…The RECEPTOR-LIKE PROTEIN 44 (RLP44) was previously described to play a role in cell wall integrity sensing via modulation of brassinosteroid-mediated responses (Wolf et al, 2014). It directly interacts with both BRI1 and BAK1 (Wolf et al, 2014;Holzwart et al, 2018) (Holzwart et al, 2019). A recent study also showed that RLP44 plays a role in vascular development, which involves phytosulfokine hormone signalling (Holzwart et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It directly interacts with both BRI1 and BAK1 (Wolf et al, 2014;Holzwart et al, 2018) (Holzwart et al, 2019). A recent study also showed that RLP44 plays a role in vascular development, which involves phytosulfokine hormone signalling (Holzwart et al, 2018). The phospho-state of the short, C-terminal tail of RLP44 is important for the interaction with BRI1 and determines, whether RLP44 is located at the PM or internalized into intracellular compartments (Garnelo Gomez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%